Modelamiento para la simulación y control del proceso de destilación por arrastre con vapor para obtener aceite esencial de limón - González Reyna, Bárbara Milagros (2013)
It is developed a mathematical model of an evaporator and a simulation for the system of non ideal behavior of steam entrainment of the lemon essential oil (AEL), for it has been realized a program in Visual Basic having as source of input and output data to the Microsoft Excel. The control of the system was performed on the temperature of the process by acting on the flow of injected steam to produce the entrainment, which is the heat source needed to produce the phenomenon. The steam trawl applied for the recovery of AEL is a unitary operation in batches and to develop the system of differential equations the Euler method is used. The program reports the data through tables and graphs of system temperature curves, vapor pressure, accumulated mass, output, liquid level, heat supplied and recovery at any time as a function of operating time. The control program shows the behavior of the system against the disturbances produced by moving the set point temperature and the graphs of the internal phenomena produced, and allows us to compare parameters of proportional integral proportional comptrollers ( PID)